(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
Metabolic diseases such as diabetes mellitus and obesity have become major global health concerns due to their increasing prevalence and significant impact on cardiovascular health. This article explores the effects of these conditions on the myocardium, the muscular tissue of the heart. Diabetes leads to metabolic dysfunction in myocardial cells, promoting oxidative stress, inflammation, and eventual structural remodeling—a condition often referred to as diabetic cardiomyopathy. Similarly, obesity contributes to myocardial damage through lipid accumulation, insulin resistance, and chronic low-grade inflammation. These changes compromise cardiac function and increase the risk of heart failure and other cardiovascular complications. Understanding the molecular and cellular mechanisms behind these effects is crucial for early diagnosis, prevention, and the development of targeted therapeutic strategies. This paper emphasizes the importance of metabolic control in preserving myocardial health in patients with diabetes and obesity.